Enterprise Architecture Design of SPBE Using TOGAF ADM for Improving Operational Efficiency: A Case Study of the Mining Sector at the West Java ESDM Agency - Dede Darsono; Shafira Febriani; Puja Rochmansyah (Journal of Electrical, Electronic, Information, and Communication Technology, 2026)
The Energy and Mineral Resources (ESDM) Agency of West Java, particularly its Mining Division, faces significant operational inefficiency challenges due to manual work processes, undocumented data management, and fragmented information systems. This condition hinders the achievement of strategic goals and compliance with the mandate of the Electronic-Based Government System (SPBE) as stipulated in Presidential Regulation No. 95 of 2018. This research aims to design an Enterprise Architecture (EA) to improve efficiency using the TOGAF ADM framework. The as-is analysis identified key problems in licensing, reporting, monitoring, and complaint services. As a solution, a to-be architecture was formulated based on the integrated E-Osmosys platform with a centralized database and API integration. Conceptual validation indicates the potential to eliminate data redundancy by up to 100% and achieve significant time efficiency improvements. The resulting blueprint provides a measurable strategic foundation for digital transformation to realize more efficient and reliable governance.